Dimensional Comparison Theory: Paradoxical relations between self-beliefs and achievements in multiple domains. (February 2015) - Marsh, Herbert W.; Lüdtke, Oliver; Nagengast, Benjamin; Trautwein, Ulrich; Abduljabbar, Adel Salah; Abdelfattah, Faisal; Jansen, Malte
Abstract: The internal/external frame of reference (I/E) model posits paradoxical relations between achievement and self-concept in mathematics and verbal domains, in which achievement in each domain has a positive effect on self-concept in the matching domain (e.g., mathematics achievement on mathematics self-concept) but a negative (contrastive) effect on self-concept in the non-matching domain (e.g., mathematics achievement on verbal self-concept). Extending the I/E model, Dimensional Comparison Theory (DCT) posits that self-evaluations are based on dimensional comparisons (e.g., how my accomplishments in one domain compare with my accomplishments in another domain) as well as the more traditional social and temporal comparisons, and on other sources of information about one's accomplishments. Extending the traditional tests of the I/E model, DCT predicts strong contrast effects only for contrasting domains that are at the opposite ends of the theoretical continuum of academic self-concept (far comparisons: e.g., the negative effect of math achievement on verbal self-concept), but much weaker negative contrast or even positive assimilation effects for complementary domains that are close to each other (near domains: e.g., positive effects of math achievement on physics self-concept; positive effects of native language on foreign language self-concept). Here we illustrate new predictions, theoretical insights, and methodology associated with DCT based on multiple academic domains (native language, foreign language, history, biology, physics and math), showing significant contrast effects for far comparisons and significantly less contrast or assimilation effects for near domains. Highlights: First test of Dimensional Comparison Theory (DCT) with diverse academic domains. Achievement has negative effects on contrasting (far) academic self-concepts (ASCs). Achievement has positive effects on matching & complementary (near) ASCs. ASCs are better differentiated and more consistent with DCT than self-efficacies.